Consequences of electrical non-neutrality of the Universe - Pustelny, Tadeusz (Opto-Electronics Review, 2025)
Photonics, optics, and optical metrology, as well as quantum optics and photonic engineering and space metrology provide us with empirical knowledge about the Universe. The theoretical description of the Universe is implemented within the framework of the so-called Standard Model. It allows for the explanation of phenomena as exotic to us as processes at distance scales thousands of times smaller than the size of a proton, but also processes in the interiors of stars, or the evolution of matter in the Universe for fractions of seconds after its creation. Thanks to optical research techniques, physical theories are being verified regarding the components of the Universe and its physical nature, as well as the processes occurring in it. It is optical observations that have provided science (and first of all – physics) with facts, the explanation of which requires answers to questions about the nature of Dark Matter and Dark Energy. This work is devoted to the search for answers about the nature of Dark Matter and Dark Energy.